Evaluation of the elasto-plastic crack tip singularities via mechano-luminescent effects. (February 2018) - Basnet, Ramesh; Timilsina, Suman; Lee, Kwang Ho; Kim, Ji Sik
Abstract: New techniques to directly evaluate the plastic singularity of elasto-plastic crack under a mixed mode from the plastic J field, as well as indirectly from an elastic K field, have been suggested using Mechano-luminescence (ML) in SrAl2 O4 :Eu, Dy. For this purpose, the ML of a plastic core, Hutchinson–Rice–Rosenberg (HRR), field in the vicinity of a physical crack tip during four-point shearing was visualized and analyzed. Plastic stress intensity factors (SIFs) of K M P measured at 829 and 872 N directly from the ML-HRR field showed proper agreement with those of K M P e that were predicted indirectly from elastic SIFs with deviations of less than 11%. An imaginary crack tip within the plastic zone and a propagating angle with the plastic zone size under transient cracking were evaluated separately to verify use of ML technique for considering elasto-plastic crack in Structural Health Monitoring (SHM).